Alcohol Production, Prevention Strategies, and Inmate Knowledge About the Risk for Botulism From Pruno Consumption in a Correctional Facility—Arizona, 2013. (October 2015) - Adams, Laura E.; Yasmin, Seema; Briggs, Graham; Redden, Kore; Silvas, Suzanne; Anderson, Shoana; Weiss, Joli; Tsang, Clarisse A.; Henke, Evan; Francies, Jessica; Herrick, Kristen; Lira, Rosa; et al.
During July to November 2012, two botulism outbreaks (12 cases total) occurred in one all-male prison; both were associated with illicitly brewed alcohol (pruno) consumption. Inmate surveys were conducted to evaluate and develop prevention and education strategies. Qualitative surveys with open-ended questions were performed among inmates from rooms where outbreaks occurred to learn about pruno consumption. Quantitative surveys assessed knowledge gained after the outbreaks and preferred information sources. For the quantitative surveys, 250 inmates were randomly selected by bed from across the correctional facility and 164 inmates were interviewed. Only 24% of inmates reported any botulism knowledge before the outbreaks and education outreach, whereas 73% reported knowledge after the outbreaks ( p < .01). Preferred information sources included handouts/fliers (52%) and the prison television channel (32%).